2012
DOI: 10.1007/s13277-012-0552-7
|View full text |Cite
|
Sign up to set email alerts
|

Density of mast cells and microvessels in minor salivary gland tumors

Abstract: The aim of this study was to investigate the density of mast cells and microvessels in minor salivary gland tumors. Forty-one cases of minor salivary gland tumors (pleomorphic adenoma, n = 10; adenoid cystic carcinoma, n = 11; mucoepidermoid carcinoma, n = 10; and polymorphous low-grade adenocarcinoma) were investigated using immunohistochemistry for mast cell tryptase and von-Willebrand factor. Density of mast cells was higher in mucoepidermoid carcinoma; however, no differences in the number of these cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 62 publications
2
25
0
Order By: Relevance
“…In another study, MVD was estimated by immunostaining with antifactor VIII antibody, in minor SGT cases (total n = 41; PA, n = 10, ACC, n = 11; MEC, n = 10; PLGA, n = 10). The highest value found in MEC, while significant differences were found in MVD values between MEC and ACC compared to PA and PLGA [44]. In a more recent study by Faur et al, conducted on 45 benign (PA, n = 8; Warthin tumor, n = 7; Basal cell adenoma, n = 5) and 25 malignant (CXPA, n = 6; MEC, n = 6 ANC, n = 5; ACC, n = 4; adenocarcinoma not otherwise specified [ADC NOS], n = 4) SGTs, high MVD values (CD34 staining) were noted for benign, especially in Warthin's tumors, and reduced values in malignant tumors [45].…”
Section: Mvd and Sgtmentioning
confidence: 81%
“…In another study, MVD was estimated by immunostaining with antifactor VIII antibody, in minor SGT cases (total n = 41; PA, n = 10, ACC, n = 11; MEC, n = 10; PLGA, n = 10). The highest value found in MEC, while significant differences were found in MVD values between MEC and ACC compared to PA and PLGA [44]. In a more recent study by Faur et al, conducted on 45 benign (PA, n = 8; Warthin tumor, n = 7; Basal cell adenoma, n = 5) and 25 malignant (CXPA, n = 6; MEC, n = 6 ANC, n = 5; ACC, n = 4; adenocarcinoma not otherwise specified [ADC NOS], n = 4) SGTs, high MVD values (CD34 staining) were noted for benign, especially in Warthin's tumors, and reduced values in malignant tumors [45].…”
Section: Mvd and Sgtmentioning
confidence: 81%
“…Katopodi et al 17 demonstrated that MCC in PA is greater than canalicular adenoma and many other authors have reported that MCs are present in epithelial cell layer of Warthin’s tumor. 19 Accumulation of MCs has been attributed to migration of MCs from surrounding connective tissue or from blood vessels. 23 MC accumulation in this area promotes tumor progression via different pathways, including an increase in angiogenesis, degrading extracellular matrix and basement membrane proteins that facilitate tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The average of MCC was separately measured in peri- and intra-tumoral areas. 12,19 In the normal SGs, MCC was evaluated in connective tissue between the epithelial components and the capsular area. Data were analyzed using SPSS 11 by t-test and Mann-Whitney and Krusskal-Wallis tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have allowed substantial progress in understanding the role of MCs in tumorigenesis and progression but further studies are necessary to completely elucidate their impact on the pathophysiology of cancer [30,31,32,33,34,35,36,37]. …”
Section: Mast Cells In Cancermentioning
confidence: 99%